2015
DOI: 10.21608/jpp.2015.51741
|View full text |Cite
|
Sign up to set email alerts
|

Response of Potato Growth and Yield to Some Stimulating Compounds.

Abstract: Two field experiments were carried out at the private Farm in Basandela Village, Belqas, Dakahlia Governorate during the two successive summer seasons of 2012 and 2013 to study the response of potato (c.v. Valor) growth and yield to some stimulating compounds i.e, Thiamine(V.B1)100 ppm, Riboflaphine(V.B2)100 ppm, Ascorbic acid (V.C)100 ppm, Decenyl succinic acid (DSA) 400 ppm, Arginine acid 400 ppm, Proline acid 400 ppm and Micronutrients (Fe, Zn and Mn) each 75 ppm. Results indicated that plant height and num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
3
2
0
1
Order By: Relevance
“…The higher content of K in plant tissue explains the higher chemical and physical quality of the cauliflower heads due to the presence of K which acts on photosynthate translocation from the leaves to the storage organs. These results come along with many previous studies which have proven that amino acids can directly or indirectly affect the vital activities of plants, as well as amino acids, play a big role in increasing the chlorophyll content in plants 31,32 . The foliar application of amino acids caused an increment of N, P, K and other micro-elements 31,32 .…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The higher content of K in plant tissue explains the higher chemical and physical quality of the cauliflower heads due to the presence of K which acts on photosynthate translocation from the leaves to the storage organs. These results come along with many previous studies which have proven that amino acids can directly or indirectly affect the vital activities of plants, as well as amino acids, play a big role in increasing the chlorophyll content in plants 31,32 . The foliar application of amino acids caused an increment of N, P, K and other micro-elements 31,32 .…”
Section: Resultssupporting
confidence: 82%
“…These results come along with many previous studies which have proven that amino acids can directly or indirectly affect the vital activities of plants, as well as amino acids, play a big role in increasing the chlorophyll content in plants 31,32 . The foliar application of amino acids caused an increment of N, P, K and other micro-elements 31,32 . Shekari and Javanmardi 33 found that foliar application of amino acid at suitable concentration had positive effects on the physical and chemical properties of broccoli plants.…”
Section: Resultssupporting
confidence: 82%
“…It is reported that proline has significant function in stabilizing osmotic effects by balancing of ion concentrations such as Na, K, Mg, and Ca in strengthening the cell wall and in other enzymatic actions (Iba, 2002). Gouda et al (2015) on potato and El-Saadony et al (2017) on pea, found that spraying plants with proline at 100 ppm gave the best growth and yield than unsprayed plants.…”
Section: Introductionmentioning
confidence: 99%
“…Ascorbic acid has a wide range of important roles in plant such as photoprotection, regulation of photosynthesis, affects nutritional cycle's activity, electron transport system, as antioxidant defense and a cofactor for a large number of key enzymes in plants, developmental senescence, programmed cell death and responses to pathogens (Blokhina et al, 2003). Foliar application of ascorbic acid previously increased plant height, leaves number, dry weight of plant and total yield (El-Sayed, 1991) on potato, (El-Morsy et al, 2010) on garlic and (Gouda et al, 2015) on potato, and increased bulbing ratio as well as average bulb weight and diameter and clove weight (El-Morsy et al, 2010) on garlic.…”
Section: Introductionmentioning
confidence: 99%